Canada : 2010 Article IV Consultation-Staff Supplement; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
A credible framework for macroeconomic policy, strong policy response, and resilient financial system have enabled Canada to exit the global crisis on a strong footing. Executive Directors encouraged authorities to maintain their prudent and far-sighted policies while strengthening productivity and competitiveness. Directors welcomed its accommodative stance of monetary policy and ambitious fiscal consolidation plans to strengthen its long-term economic potential. They observed that Canada is well positioned to adapt its financial regulatory framework to emerging international initiatives. Further progress toward national securities regulation will be an essential enhancement in this framework.